1995
DOI: 10.1139/g95-118
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus analysis of fatty acid concentrations in maize

Abstract: A study was conducted to determine the number and chromosomal location of quantitative trait loci (QTL) influencing the concentration of five fatty acids in 200 F2S1 lines derived from an Illinois High Oil (IHO) by Illinois Low Oil (Early Maturity) (ILO(EM)) cross. Restriction fragment length polymorphism (RFLP) analysis was performed on the 200 S1 lines and concentrations of palmitic (16:0), stearic (18:0), oleic (18:1), linoleic (18:2), and linolenic (18:3) acids were determined in self-pollinated kernels ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
1
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 28 publications
4
41
1
3
Order By: Relevance
“…W h e n a11 data are combined, a statistically significant increase is obtained. Furthermore, the increase in 18:l content is consistent with results i n maize, indicating a positive correlation between total seed oil content a n d 18:l percentages (Alrefai et al, 1995).…”
Section: Scussl Onsupporting
confidence: 86%
“…W h e n a11 data are combined, a statistically significant increase is obtained. Furthermore, the increase in 18:l content is consistent with results i n maize, indicating a positive correlation between total seed oil content a n d 18:l percentages (Alrefai et al, 1995).…”
Section: Scussl Onsupporting
confidence: 86%
“…However, more recently, several studies have demonstrated positive correlations between grain protein and oil contents (Dudley and Lambert, 2004;Wassom et al, 2008;Zhang et al, 2008). Further research has attempted to reveal the genetic mechanisms underlying kernel composition traits by mapping QTLs using different genetic germplasms such as IHP and ILP (Goldman et al, l993;, IHO and ILO (Alrefai et al, 1995;Berke and Rocheford, 1995;Laurie et al, 2004;Willmot et al, 2006;Wassom et al, 2008), Beinongda high-oil (BHO) (Song et al, 2004;Zhang et al, 2008), tropical high-oil (Mangolin et al, 2004), Alexho Single-Kernel (ASK) high-oil (Zheng et al, 2008;Li et al, 2009;Wang et al, 2010;Yang et al, 2012), and popcorn (Liu et al, 2008) maize populations. Based on data obtained from these studies and from the public genetic linkage map of maize (www.maizegdb.org), 79 QTLs for grain protein content and 52 QTLs for grain oil content have been detected.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of molecular markers and the development of quantitative trait loci (QTL) mapping procedures, genes that control storage lipid synthesis can be identified and marker-assisted selection used to move beneficial QTL alleles into elite agricultural genotypes in oilseed breeding programs (Lande and Thompson, 1990). QTL analyses of oil content have been made in a number of crops, including oilseed rape (Brassica napus; Ecke et al, 1995;Burns et al, 2003), soybean (Glycine max; Lee et al, 1996;Csanadi et al, 2001), maize (Zea mays; Alrefai et al, 1995), and sunflower (Helianthus annuus; Mokrani et al, 2002;Leon et al, 2003). An analysis of groat oil content in oats revealed the presence of a small number of QTLs and an association between the major QTL and the plastidic acetyl-CoA carboxylase gene (Kianian et al, 1999).…”
mentioning
confidence: 99%
“…In Arabidopsis, mutagenesis experiments facilitated the identification of genes responsible for fatty acid elongation and desaturation (James and Dooner, 1990;Lemieux et al, 1990;Arondel et al, 1993;Okuley et al, 1994;James et al, 1995). Since then, QTL affecting fatty acid composition that colocate with loci for fatty acid elongase and fatty acid desaturase genes have been identified in Brassica species, sunflower, and maize (Alrefai et al, 1995;Ecke et al, 1995;Jourdren et al, 1996;Cheung et al, 1998;Fourmann et al, 1998;Lionneton et al, 2002;Perez-Vich et al, 2002;Burns et al, 2003;Mikkilineni and Rocheford, 2003).…”
mentioning
confidence: 99%